Regional industrial policy in times of big disruption: building dynamic capabilities in regions. Issue 10 (2nd November 2021) - Labory, Sandrine; Bianchi, Patrizio
ABSTRACT: This paper contributes to the literature by proposing that regions have to develop dynamic capabilities in order to successfully adapt to big disruption such as Industry 4.0. It explores both the strategic management and the regional studies literatures to explore why, how and what dynamic capabilities might be deployed at a regional level. The theoretical insights are illustrated in the case of the Emilia-Romagna region in Italy. Dynamic capabilities appear both to mediate between structure and agency in regional path development and to promote value creation and capture. Their consideration in Research and Innovation Strategies for Smart Specialisation (RIS3) might favour policy implementation besides policy definition.